ERRORS OCCURED IN THE ESSAYS OF IALF STUDENTS - Aryadi Jaya, I Putu (Lingual: Journal of Language and Culture, 2015)
Investigating the interference found in the essays of a few IALF (Indonesia Australia Language Foundation) students is quite interesting and challenging because it can be found what factors that affect the students in English communication and lead to the interference. The purpose of this study is to analyze the causes of the interference which occurs in the IALF studentsâ essays and the implication of the interference found. The qualitative descriptive analysis strategy model is applied in this small study to get an idea of which aspects of linguistics that experience interference. The findings reveal that there are various aspects of linguistics that experience interference in essays. Among them are the selection of lexicons syntactically, the use of lexicons in semantics, lexicon order, sentence structure, and the use of copula